THE INFLUENCE OF GREEN ADVERTISING AND GREEN CLAIM TOWARD GREEN TRUST WITH MISLEADING ENVIRONMENTAL CLAIM AS INTERVENING VARIABLE OF AQUA PRODUCT ON FACULTY OF ECONOMICS AND BUSINESS UNSRAT STUDENT - Sariputri, I Dewa Ayu; Lapian, Joyce S.L.H.V.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Aqua is a company which has released some green advertising and have green claim on its packaging. This study aims to find out the influence of green advertising and green claim toward green trust with misleading environmental claim as intervening variable of bottled water product Aqua. The amount of respondents are 100 people, and the respondents are the students from Faculty of Economics and Business Sam Ratulangi University who are consumers of Aqua product and ever seen Aqua advertisements before. The sampling technique in this study used purposive sampling with path analysis method. The result shows that (1) green advertising and green claim have negative significant influence toward misleading environmental claim of Aqua product, (2) green advertising and green claim have positive significant influence toward green trust of Aqua product, (3) misleading environmental claim has significant influence as intervening of green advertising variable toward green trust of Aqua product, (4) misleading environmental claim has no significant influence as intervening of green advertising variable toward green trust of Aqua product. This study suggests that Aqua should develop the content of its green advertising, put some clear information about the green claims and prevent the issue of greenwashing.Keywords: green advertising, green claim, misleading environmental claim, green trust